2021
DOI: 10.1016/j.acra.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Pass/Fail USMLE Step 1 Scoring—A Radiology Program Director Survey

Abstract: Rationale and Objectives: In February 2020, administrators for the US medical licensing examination (USMLE) announced that Step 1 reporting would change to pass/fail in hopes of reducing the overemphasis of USMLE performance on the residency selection system and improving medical student well-being. Our objective was to determine the perspectives of diagnostic radiology (DR), interventional radiology (IR), and nuclear medicine (NM) program directors (PDs) regarding pass/fail USMLE Step 1 scoring. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The aim of this study was to compare the perceptions among program directors (PDs) in orthopaedics and IM on the change of Step 1 from a graded to a pass/fail exam, and its impact on the residency application process. Some groups have studied PD opinions of the Step 1 pass/fail change; however, to the best of our knowledge, the current study is the first comprehensive survey to directly compare the impact on medicine and a surgical subspecialty [4][5][6][7][8][9][10][11][12]. We chose to study IM PDs because IM has historically been a popular specialty that has had the most number of total applicants.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to compare the perceptions among program directors (PDs) in orthopaedics and IM on the change of Step 1 from a graded to a pass/fail exam, and its impact on the residency application process. Some groups have studied PD opinions of the Step 1 pass/fail change; however, to the best of our knowledge, the current study is the first comprehensive survey to directly compare the impact on medicine and a surgical subspecialty [4][5][6][7][8][9][10][11][12]. We chose to study IM PDs because IM has historically been a popular specialty that has had the most number of total applicants.…”
Section: Introductionmentioning
confidence: 99%
“…While this change is technically independent of virtual interviewing, how it will impact ranking remains to be seen, given the mixed reception from program directors. [11] It has been further suggested that additional criteria must be considered, including interpersonal and communication skills, professionalism, and the overall fit of an applicant at the unique program. [7] These attributes clearly influence the ranking process, yet it is already difficult to evaluate these skills by reading an application and then interviewing in-person, not to mention virtually.…”
Section: Discussionmentioning
confidence: 99%
“…In February 2020, it was announced that there would be a movement away from a numerical score on the US Medical Licensing Examination (USMLE) Step I to pass/fail, beginning in 2022. 10 This was promulgated by the overwhelming desire to improve student well-being and that the USMLE examinations (Step I and II) were not developed for evaluation of student academic achievement but rather licensure. 11 There were additional reasons for this change.…”
Section: A J P Ementioning
confidence: 99%